Pengaruh Lingkungan Kerja dan Stres Kerja terhadap Produktivitas Kerja Karyawan Studi Kasus pada PT. Telkom Witel Bekasi - Chintya Aprilianti; Melyani (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2024)
The purpose of this study is to understand how work stress and work environment affect employee work productivity simultaneously and proportionately. The purpose of this case study is to determine the important variables that cause the productivity of PT. Telkom Witel Bekasi's workers. In this case study, a saturated sampling method is used, which means that each member of the population is used as a sample from a relatively small population. The study involved 47 workers. Validity, reliability, linear multiple regression, and classical assumptions such as normality, heteroscedasticity, and multicollinearity are used. The hypothesis was then tested with the F and T tests.  Data was collected through questionnaires. The results of the hypothesis test show that stress and the work environment have a positive and significant impact on employee performance. The results of multiple regression analysis also show that stress and work environment have a positive and significant effect on productivity. In addition, hypothesis tests show that there is a positive and significant impact on employee work productivity greatly increased. Therefore, companies must always reduce stress in the workplace, even create a more stress-free environment, and build a better working atmosphere to increase employee productivity.